Exploring the Dynamics of Maguindanaon Kawing (Marriage): A Keystone to Understanding Culture and Traditions - Karim, Jerald; Mallo, Erwin (Journal of Interdisciplinary Perspectives, 2026)
Unveiling the dynamics of Maguindanaon Kawing (Marriage) underscores the religious and social values of Maguindanaon culture and traditions. This study examines the observation of Maguindanaon kawing. Using a phenomenological approach, insights were collected from interviews with Ustads and Kamals, who served as key informants of the study. The results provide significant insights into Maguindanaon Kawing practices over the past few years. Kawing is a notable cultural practice that involves spiritual and logistical guidance. It emphasizes the crucial role of Kamals and Ustads in formalizing the traditional sanctity of kawing, which is not only for a marital ceremony but also represents the community's religious and social values. Kawing is a sacred ritual that testifies to Maguindanaon identity and renders any practice outside it haram. Moreover, the step-by-step process of Kawing includes symbolic and traditional portrayals, such as whispering, panangguni, salangguni, and proper Kawing. However, changes in Kawing practices are evident, including increased Mah'r and distance relationship practices, which are influenced by evolving societal and economic factors. In addition, some practices are no longer observed, like the Kulo, sleeping together after marriage, rush weddings, and damak. The Ustads and Kamals emphasized that the process must be followed and valued, as it embodies the essence of kawing identity within their distinct cultural representations. The findings highlight the roles portrayed by Ustads and Kamals (in preservation, procedural validity, and authority) and the avoidance of Zina. It further encourages future studies to preserve practices, including those in Arabic schools, to gain knowledge of Kawing and to promote the participation of male Maguindanaon in preparing to be the Ustads or Kamals of their community.